The opinion of the Expert Group of the Polish Society of Ophthalmology on using nepafenac in the prevention of postoperative macular edema after cataract surgery in diabetic patients – update - Grabska-Liberek, Iwona; Bakunowicz-Łazarczyk, Alina; Malukiewicz, Grażyna; Misiuk-Hojło, Marta; Mrukwa-Kominek, Ewa; Romaniuk, Wanda; Romanowska-Dixon, Bożena; Jurowski, Piotr; Kęcik, Dariusz; Lubiński, Wojciech; Omulecki, Wojciech; Szaflik, Jerzy; et al. (Klinika Oczna / Acta Ophthalmologica Polonica, 2018)
Diabetic patients constitute a high risk group for developing macular edema after cataract surgery. Nepafenac (available as 0.1% and 0.3% chemical strength) is an innovative non-steroidal anti-inflammatory drug used in ophthalmology for the prevention of macular edema after cataract surgery. Along with its anti-inflammatory effect, nepafenac has some unique properties which distinguish it from other non-steroidal anti-inflammatory drugs. It is a prodrug activated to amfenac after it penetrates through the corneal layers to the aqueous humour and the ciliary body. Having electrically neutral molecules of lipophilic properties, nepafenac does not accumulate in the cornea and does not cause its degeneration. Additionally, it quickly achieves higher concentrations in the aqueous humour as compared to other non-steroidal anti-inflammatory drugs. Nepafenac shows high selectivity and activity against COX-2 isoform, the key enzyme implicated in inducing inflammation, which is the main cause of macular edema. Furthermore, nepafenac has the unique scleral and suprachoroidal distribution pathways. Finally, its effect on the intraocular pressure is none to negligible. Nepafenac treatment should be initiated prior to cataract surgery and continued long enough to reduce the risk of late-onset macular edema. The Expert Group of the Polish Society of Ophthalmology consider using nepafenac in the prevention of postoperative macular edema in diabetic patients undergoing cataract surgery as expedient and reasonable. The proposed optimum pre- and postoperative treatment regimen can be modified for individualised therapy.